Beyond the classic eicosanoids: Peripherally-acting oxygenated metabolites of polyunsaturated fatty acids mediate pain associated with tissue injury and inflammation. (August 2016) - Shapiro, Haim; Singer, Pierre; Ariel, Amiram
Abstract: Pain is a complex sensation that may be protective or cause undue suffering and loss of function, depending on the circumstances. Peripheral nociceptor neurons (PNs) innervate most tissues, and express ion channels, nocisensors, which depolarize the cell in response to intense stimuli and numerous substances. Inflamed tissues manifest inflammatory hyperalgesia in which the threshold for pain and the response to painful stimuli are decreased and increased, respectively. Constituents of the inflammatory milieu sensitize PNs, thereby contributing to hyperalgesia. Polyunsaturated fatty acids undergo enzymatic and free radical-mediated oxygenation into an array of bioactive metabolites, oxygenated polyunsaturated fatty acids (oxy-PUFAs), including the classic eicosanoids. Oxy-PUFA production is enhanced during inflammation. Pioneering studies by Vane and colleagues from the early 1970s first implicated classic eicosanoids in the pain associated with inflammation. Here, we review the production and action of oxy-PUFAs that are not classic eicosanoids, but nevertheless are produced in injured/ inflamed tissues and activate or sensitize PNs. In general, oxy-PUFAs that sensitize PNs may do so directly, by activation of nocisensors, ion channels or GPCRs expressed on the surface of PNs, or indirectly, by increasing the production of inflammatory mediators that activate or sensitize PNs. We focus on oxy-PUFAs that act directly on PNs. Specifically, we discuss the role of arachidonic acid-derived 12S-HpETE, HNE, ONE, PGA2, iso-PGA2 and 15d -PGJ2, 5, 6-and 8, 9-EET, PGE2 -G and 8R, 15S-diHETE, as well as the linoleic acid-derived 9-and 13-HODE in inducing acute nocifensive behavior and/or inflammatory hyperalgesia in rodents. The nocisensors TRPV1, TRPV4 and TRPA1, and putative Gαs-type GPCRs are the PN targets of these oxy-PUFAs.